Recent Updates in Vaccine Delivery through Microneedles - Kasturi Pawar (Tabriz University of Medical Sciences, 2023)
Recent coronavirus pandemic and its global socio-economic impact has re-emphasized the need for safe, fast, and efficient delivery of vaccines for humankind. With advent of technological advances, and to improve patient acquiescence, several techniques for fast, effective, and safe delivery of vaccines have been researched and published in the literature in last three decades. These delivery enhancement techniques include but are not limited to electroporation, microneedles (MN), ultrasound, iontophoresis, etc. This review aims at discussing the current research undergoing in vaccine delivery, specifically focusing on microneedles assisted, the historical background of microneedles and their introduction to drug delivery area, and a special focus on formulation challenges and stability in these systems. The review also sheds light on regulatory challenges one must keep in mind for bringing a successful microneedles-based vaccine delivery into market as well as a snapshot of current commercially available microneedles-based products in cosmetic and pharmaceutical industry.